Instagram and Social Media's Influence on Indonesian Vocational School Adolescents' Hedonistic Lifestyle - Veno Dwi Krisnanda; Kadek Suhardita; Laily Tiarani Soejanto; I Made Suarta; Raup Padillah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Hedonistic One of a person's life's objectives is to pursue pleasure only, which is a problem that many young people face. people confront. This arose as a result of the current expansion of social media in industrialisation and globalization. The Instagram app, which can be used to communicate numerous occasions through photographs and videos, is one method to use social media. The goal of This study seeks to quantify the influence of Instagram on the hedonistic lifestyle. In this study, a sample of 70 respondents was employed, and a questionnaire was used in the information gathering process. The equation Y= 7. 855+ 0. 732X is the outcome of linear regression analysis, and the correlation coefficient (r) between the variables X and Y produced a correlation coefficient value of 0. 74. This value indicates that there is a significant and favorable correlation between the two variables. 54. 76% of the Hedonism Lifestyle is affected by Instagram, with the remaining 25. 99% influenced by other factors not examined in this study